SEASONAL VARIATIONS IN AIR POLLUTION TOLERANCE INDEX IN SOME SELECTED PLANT SPECIES (International Journal of Food and Nutritional Sciences, 2022)
Some plant species are tolerant to air pollution and other plant species are susceptible to air pollution. Susceptible plant species are considered as air pollution indicators whereas tolerant plant species considered for green belt development. In this study the seasonal variations in Air Pollution Tolerance Index was assessed by taking 18 plant species such as Pongamia pinneta, Bougainvillea glabra, Tinospora cardifolia, Hibiscus rosasinencis, Lantana camara, Annona reticulata, Syzygium cumini, Couroupita guianensis, Baliospermum solanifolium, Catharanthus roseus, Ficus religiosa, Azadirachta indica, Senna auriculata, Casia fistula, Albizia lebbeck, Pdilanthus tithimiloides, Psidium guava, Mangifera indica that are commonly available in the selected study area. Among the studied plant species physicochemical parameters such as total chlorophyll content, leaf extract pH, relative water content and ascorbic acid are recorded as these are responsible for changing APTI ( Air pollution Tolerance index) values. These changes were observed during three seasons in a year. The highest APTI values were found during winter season followed by monsoon and summer season. Among the plant species studied, the highest APTI value was found in Mangifera indica (15.89) during winter season and lowest APTI value was found in Baliospermum solanifolium( 6.73) during summer season.